2013
DOI: 10.4097/kjae.2013.64.6.517
|View full text |Cite
|
Sign up to set email alerts
|

Palonosetron has superior prophylactic antiemetic efficacy compared with ondansetron or ramosetron in high-risk patients undergoing laparoscopic surgery: a prospective, randomized, double-blinded study

Abstract: BackgroundPostoperative nausea and vomiting (PONV) continues to be a major problem, because PONV is associated with delayed recovery and prolonged hospital stay. Although the PONV guidelines recommended the use of 5-hydroxy-tryptamine (5-HT3) receptor antagonists as the first-line prophylactic agents in patients categorized as high-risk, there are few studies comparing the efficacies of ondansetron, ramosetron, and palonosetron. The aim of present study was to compare the prophylactic antiemetic efficacies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 31 publications
(31 reference statements)
4
65
0
Order By: Relevance
“…Palonosetron, a 5-HT3 antagonist with a half-life of 40 h and improved side-effect profile compared with others in its class, has been demonstrated to be superior to ondansetron, ramosetron and placebo for postoperative nausea prevention 2 3. Highlighting the complexity of treating refractory nausea, this case describes palonosetron being successfully used for nausea and vomiting, as well as class switching and switching therapy within classes.…”
Section: Discussionmentioning
confidence: 97%
“…Palonosetron, a 5-HT3 antagonist with a half-life of 40 h and improved side-effect profile compared with others in its class, has been demonstrated to be superior to ondansetron, ramosetron and placebo for postoperative nausea prevention 2 3. Highlighting the complexity of treating refractory nausea, this case describes palonosetron being successfully used for nausea and vomiting, as well as class switching and switching therapy within classes.…”
Section: Discussionmentioning
confidence: 97%
“…We then retrieved the full texts of the remaining 16 citations and excluded seven of these citations because five among them had no intended interventions and two had no outcomes of interest. Altogether, nine studies [25][26][27][28][29][30][31][32][33] fulfilled the criteria for systematic review and meta-analysis. The study selection processes are shown in Fig.…”
Section: Study Selectionmentioning
confidence: 99%
“…Reports of recent clinical studies 30,[39][40][41] showed that granisetron, ramosetron, and palonosetron had similar rates of associated adverse effects when used to prevent PONV, and in general, the incidence of common adverse events seemed to be similar among different 5-HT 3 RAs. With regard to serious adverse events, however, significant differences between palonosetron and ondansetron may exist.…”
Section: A Early Ponmentioning
confidence: 99%
See 2 more Smart Citations